2007
DOI: 10.1109/tbme.2006.886617
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Biocompatibility of Chronically Implanted Polyimide and Platinum Intrafascicular Electrodes

Abstract: Longitudinal intrafascicular electrodes (LIFEs) are electrodes designed to be placed inside the peripheral nerve to improve stimulation selectivity and to increase the recording signal-to-noise ratio. We evaluated the functional and morphological effects of either Pt wire LIFEs or polyimide-based thin-film LIFEs implanted in the rat sciatic nerve for 3 mo. The newly designed thin-film LIFEs are more flexible, can be micromachined and allow placement of more active electrode sites than conventional Pt LIFEs. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
163
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 202 publications
(177 citation statements)
references
References 29 publications
9
163
0
Order By: Relevance
“…An understanding of this organization is critical for the design of penetrating peripheral nerve electrodes. It has been previously observed that these types of electrodes are accompanied by a chronic inflammatory response including the recruitment of macrophages to the device interface (Klinge et al, 2001;Lago et al, 2007;Christensen et al, Fig. 5.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…An understanding of this organization is critical for the design of penetrating peripheral nerve electrodes. It has been previously observed that these types of electrodes are accompanied by a chronic inflammatory response including the recruitment of macrophages to the device interface (Klinge et al, 2001;Lago et al, 2007;Christensen et al, Fig. 5.…”
Section: Discussionmentioning
confidence: 91%
“…The composition of the rat sciatic nerve has been relatively well studied and morphometric parameters for myelinated fibers, such as fascicle area (Podhajsky and Myers, 1993;Di Benedetto et al, 1998), fiber count (Jenq and Coggeshall, 1985a,b;Jenq et al, 1986;Schmalbruch, 1986;Rodrıguez et al, 2000;Ceballos et al, 2002;Rafiuddin Ahmed and Jayakumar, 2003;Lago et al, 2005Lago et al, , 2007Prodanov and Feirabend, 2007), fiber density (number of myelinated fibers per fascicle unit area) (De Angelis et al, 1994;Rodrıguez et al, 2000;Mazzer et al, 2008), fiber packing (the percent of the fascicular area occupied by myelinated fibers) (Koller et al, 1992), mean fiber diameter (Le Beau et al, 1988;Koller et al, 1992;De Angelis et al, 1994;Di Benedetto et al, 1998;Prodanov and Feirabend, 2007), fiber diameter distributions (Strain and Olson, 1975;Schmalbruch, 1986;Wehling et al, 1992;Rodrıguez et al, 2000;Prodanov and Feirabend, 2007;Mazzer et al, 2008), and mean g-ratio (Adhami et al, 1976;De Angelis et al, 1994;Di Benedetto et al, 1998;Rodrıguez et al, 2000;Rafiuddin Ahmed and Jayakumar, 2003;Mazzer et al, 2008) or g-ratio distributions (Mazzer et al, 2008), have been described (Table 1). It is important to recognize that such data have been collected from multiple strains and from rats of varying ages, variables whose influence on morphometric parameters have not been exami...…”
mentioning
confidence: 99%
“…A 30 nm Pt layer was then deposited using electron beam evaporation and patterned using a lift-off technique. The Pt was used as the electrode material due to its chemical stability under an electrical bias in a salt solution [25]. A second polyimide layer (5 µm thick) was applied and imidized, and acted as an insulation layer between the electrodes.…”
Section: Fabrication Of Flexible Microelectrodesmentioning
confidence: 99%
“…3) is made of a thin, strip-like polyimide structure that is folded during the implantation process in the same way as the tf-LIFE implantation [33]. This creates a double-sided electrode with 10 Platinum (Pt) circular active sites (or poles), five for the left side (named L1 to 5) and five for the right side (named R1 to 5, see for details [29]).…”
Section: B Time Designmentioning
confidence: 99%